2018
DOI: 10.1088/1361-6528/aaa687
|View full text |Cite
|
Sign up to set email alerts
|

Condition optimization for exfoliation of two dimensional titanium carbide (Ti3C2T x )

Abstract: The new class of 2D MXene material exfoliated from transition metal carbides receives increasing research interest due to its extraordinary properties and high potential in energy and environmental applications. However, the exfoliation of TiCT , a widely studied MXene, from its precursor TiAlC by chemical etching in HF solution remains to be optimized. This study investigated the optimum exfoliation condition through systematic evaluating potential effects of reaction parameters, including the weight ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…The formation of 1 O 2 does not involve electron transfer. [61,63] Our results indicated that both UV and visible light could cause Ti 3 C 2 T x flakes to enter an excited state, promoting a shift from groundstate O 2 to 1 O 2 ; however, the HMH and KOH treatments (particularly the HMH treatment) may inhibit this process to some extent. Unlike the generation of 1 O 2 , the formation of O 2…”
Section: Ros Formationmentioning
confidence: 75%
See 3 more Smart Citations
“…The formation of 1 O 2 does not involve electron transfer. [61,63] Our results indicated that both UV and visible light could cause Ti 3 C 2 T x flakes to enter an excited state, promoting a shift from groundstate O 2 to 1 O 2 ; however, the HMH and KOH treatments (particularly the HMH treatment) may inhibit this process to some extent. Unlike the generation of 1 O 2 , the formation of O 2…”
Section: Ros Formationmentioning
confidence: 75%
“…[63] Self-combination with H 2 O serves as a major degradation process for O 2 − , which results in the formation of H 2 O 2 and the production of •OH. [61] The lower concentrations of O 2 − and •OH detected in the HMH-Ti 3 C 2 and KOH-Ti 3 C 2 suspensions could be due to the reduced electron donation caused by the adsorption of HMH molecules or K + ions. The differences in the ROS production between the three MXene flakes could be attributed to their different surface modifications and resulted in a photochemical stability sequence of HMH-Ti 3 C 2 > KOH-Ti 3 C 2 > H 2 O-Ti 3 C 2 , which is further discussed using DFT calculation and MD simulation in the following section.…”
Section: Ros Formationmentioning
confidence: 94%
See 2 more Smart Citations
“…on the MXene surface (usually indicated as T x ) [23]. It can be realized with other etching agents (e.g., LiF + HCl conc., NH 4 F) and exfoliation methodologies (e.g., ultrasonication), but such a process can still be hardly scaled-up in a cost-effective manner due to large consumption of solvent and energy [24,25,26]. Therefore, a MC exfoliation process of the MAX phase has been also investigated by utilizing dimethyl-sulfoxide as solvent [27].…”
Section: Introductionmentioning
confidence: 99%